2022
DOI: 10.1186/s40337-022-00637-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of salivary immunoglobulins and their association with analgesic neuropeptide opiorphin in anorexia nervosa during adolescence

Abstract: Background Patients who suffer from anorexia nervosa (AN) are characterized by exceedingly lower body weight, micro- and macro-nutrient deficiencies, and hyposalivation as compared to healthy subjects. In addition, AN may predispose to difficulties in oral health maintenance. However, little is known about the relationship between stress-dependent salivary neuro/immunopeptidergic biomarkers such as opiorphin and immunoglobulins (Ig) and AN.The aim of this case–control study was to evaluate sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In a recent study, Paszynska et al (2022) have reported an increase in salivary opiorphin levels and decrease in IgM in anorexia nervosa patients, while IgA and IgG levels did not change compared to healthy controls. Similarly, ulcers caused by denture‐related trauma may alter the overall composition of the saliva.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a recent study, Paszynska et al (2022) have reported an increase in salivary opiorphin levels and decrease in IgM in anorexia nervosa patients, while IgA and IgG levels did not change compared to healthy controls. Similarly, ulcers caused by denture‐related trauma may alter the overall composition of the saliva.…”
Section: Discussionmentioning
confidence: 92%
“…have reported increased salivary opiorphin levels in children with stressful experiences in the past.The perceived stress levels were not investigated in the current study. Since pain and stress are closely related, not evaluating the stress levels can be regarded as a limitation of this study.In a recent study,Paszynska et al (2022) have reported an increase in salivary opiorphin levels and decrease in IgM in anorexia nervosa patients, while IgA and IgG levels did not change compared to healthy controls. Similarly, ulcers caused by denture-related trauma may alter the overall composition of the saliva.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Inflammatory cytokines that maintain chronic inflammation and reflect activation of inflammatory cells are potential markers helpful in the diagnosis and monitoring of SS and associated comorbidities. Previous studies revealed changes in the inflammatory cytokine profile due to inflammation of the salivary glands in patients with eating disorders such as anorexia [3]. Apart from their traditional pro-inflammatory or anti-inflammatory function, cytokines play a multifactorial and complex role in other processes including the initiation of vascular endothelial damage, lipoprotein metabolism changes, inducing a proatherosclerotic profile and insulin resistance as well as the thrombosis promotion by the secretion of procoagulant factors [4].…”
Section: Introductionmentioning
confidence: 99%